ANALISIS KINERJA PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN GRESIK DENGAN PENDEKATAN BALANCED SCORECARD - FITRIA KUSUMAWATI, EKA Fitria (Jurnal Akuntansi AKUNESA, 2013)
In the face of an increasingly complex business environment required performancemeasurement methods that can assess the company's performance accurately and thoroughly,method can be used is the Balanced Scorecard. This study aims to measure the performanceof Perusahaan Daerah Air Minum (PDAM) Kabupaten Gresik by using the concept ofBalanced Scorecard with the four perspectives, namely financial perspective, customerperspective, internal business process perspective and learning and growth perspective.Research case study, data collection using primary data and secondary data. Primary dataobtained from questionnaires using simple random sampling technique which is obtainedfrom employees and customers of PDAM Kabupaten Gresik, and secondary data obtainedfrom company annual reports over a period of five years ie 2006 to 2010. The results of thesequestionnaires have been tested the validity and reliability. From this research it is knownthat the financial perspective can be quite good, the customer's perspective has a pretty goodperformance, internal business process perspective shows that good corporate performance,and learning and growth perspective can be said to be less good.Keywords : Balanced Scorecard, Financial Perspective, Customer Perspective, InternalBusiness Process Perspective, Learning and Growth Perspective.